High Resolution 3-D Imaging - Chiang, C. T.; Chung, B. K. (2005)
A three dimensional radar image can be constructed from scanning microwave measurements. A Vector Network Analyzer has been used for wideband phase and magnitude measurements of radar return. Quasi-monostatic horn antenna configuration is chosen to transmit and receive the electromagnetic wave. Measured target is placed on a polystyrene foam pedestal at 5 meters distance away from the 2-D planar scanner. A wide bandwidth, ranging from 3 GHz to 18 GHz gives rise to very fine range resolution. A time domain gating technique is used to remove spurious signals from the desired signal of the radar target. Range Migration Technique has been used to produce a 3-D radar image. Indoor measurements have been performed on conducting spheres to validate the software. A high resolution 3-D radar image for spheres has been obtained. Analysis of the radar cross-sections shows good correlation with theoretical values. Subsequently, the radar cross-section of an oil palm tree was measured and analyzed.